2015
DOI: 10.1890/es14-00480.1
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐soil feedbacks as drivers of succession: evidence from remnant and restored tallgrass prairies

Abstract: Plant-soil feedbacks can contribute to the coexistence of plant species and may predict the abundance of plant species within communities. Here, we test if plant-soil feedbacks act as drivers of secondary succession. We found that the strength of feedback experienced by a plant species was positively correlated with that species' successional stage, indicating that plant-soil feedbacks can contribute to shifts in plant species abundance during succession. We did not observe a significant relationship between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
136
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(157 citation statements)
references
References 43 publications
(79 reference statements)
15
136
0
Order By: Relevance
“…2). Our results further support previous studies showing differences in susceptibility and response to soil microbial communities of agricultural and pioneer plant species vs. shade-tolerant forest trees (Johnson et al 2008, Pizano et al 2014, Bauer et al 2015. 3), in support of our second hypothesis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…2). Our results further support previous studies showing differences in susceptibility and response to soil microbial communities of agricultural and pioneer plant species vs. shade-tolerant forest trees (Johnson et al 2008, Pizano et al 2014, Bauer et al 2015. 3), in support of our second hypothesis.…”
Section: Discussionsupporting
confidence: 92%
“…3), suggesting that they find species-specific soil microbes in their corresponding habitats (Appendix S1: Table S4). 3D), in support of previous studies showing that early successional species tend to exhibit negative feedbacks, while late successional species experience neutral or positive feedbacks (McCarthy-Neumann and Kobe 2008, Pizano et al 2014, Bauer et al 2015. Shade tolerant species showed no significant growth response to treatments (Fig.…”
Section: Net Effects Of Amf and Filtrate Inocula From Habitats With Dsupporting
confidence: 90%
See 1 more Smart Citation
“…This is understandable given the number of definitions introduced into the recent literature. While such concepts may help us understand the ecology of conservatism for some species, and while FQA has been used as a proxy measure for some of them (e.g., succession; Bauer et al 2015), they should not be confused with its fundamental meaning. A review of 100 randomly selected FQA publications published between 1988 and 2013 found that 88% incorrectly defined FQA, and 84% incorrectly interpreted what FQA measures (Spyreas, unpublished data).…”
Section: Wrong Definitionmentioning
confidence: 99%
“…), and likewise some studies do not find the expected relationship between the strength or direction of PSF and patterns of plant species abundance in space (Reinhart ; but see Bauer et al. for evidence that PSF predicts plant species abundances in time, along successional trajectories).…”
Section: Introductionmentioning
confidence: 96%